PERALIHAN HAK ATAS TANAH DENGAN PERJANJIAN PENGIKATAN JUAL BELI BERDASARKAN SEMA NO. 4 TAHUN 2016 (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2022)
The transfer of land rights through buying and selling according to PP No. 24 of 1997 concerning land registration states that land can be transferred if there is a Sale and Purchase Deed (AJB) made by PPAT, the development of legal facts is that there is a Sale and Purchase Binding Agreement (PPJB) based on SEMA Number 4 of 2016 that the transfer of land rights can only be transferred based on PPJB, because until now there has been no clear regulation specifically regarding PPJB in the laws and regulations, it is often questioned regarding the validity of PPJB, as well as legal protection to the parties who make it. The purpose of this study was to analyze the status of the transfer of land rights with PPJB based on SEMA No. 4 of 2016 which does not require the existence of AJB and to know the legal protection for the parties if the transfer of land rights is only with PPJB only. This study uses a normative juridical research method with an approach in the form of legislation and cases with qualitative descriptive analysis methods. The results of this study are that the status of the transfer of land rights with PPJB based on SEMA No. 4 of 2016 which does not require the existence of AJB is valid as Article 1338 of the Civil Code but does not guarantee that the transfer of land rights to other people can occur if the transfer is not carried out according to Article 1459 of the Civil Code, PPJB before AJB is allowed as long as the requirements as stipulated in the regulations are met, Meanwhile legal protection for parties who make PPJB only in the transfer of land rights is preventive legal protection, by pouring clear clauses in PPJB and repressive legal protection, the parties can resolve it until the court. Keywords: Transfer of rights, PPJB, Legal Protection